Perceptions of crisis - Statulova, Daniela (Media and Language, 2024)
The purpose of this paper is to examine the concepts of perception and crisis in historical and sociocultural terms. Also how crisis is perceived – with negative or positive reactions, respectively as a momentary malaise and suffering from the “diseases of society”, or as an occasion for change and progress in finding meaning. In a problematic situation, crisis is most often perceived as a catastrophic experience, but it has another side – it can be a good opportunity to change direction by overcoming obstacles and making a new beginning in order to achieve a new humanism. The methods of comparative analysis are used for attitudes towards crises in the ancient/modern periods, content analysis of the media language and empirical analysis in the form of a survey. It is not possible to objectively assess the perception of crisis due to the dual nature of the concept, its fluid connotation depending on the context and the blurring of boundaries in its use in everyday speech, political and public discourse, etc.
Keywords: perception; crisis; diseases of society; communication